Comparison of Pineapple Juice and Mannitol as Oral Contrast Agents for Magnetic Resonance Enterography - Ahmad Farid Zulkifle; Hamzaini Abdul Hamid; Siti Soraya Ab Rahman (Malaysia Medical Association, 2024)
Indexed by Scopus/MyCite